Analisis Perbandingan Ketelitian Pengukuran Terrestrial Laser Scanner (TLS) dan Handheld Slam Lidar untuk Pemetaan dalam Ruangan : (Studi Kasus: PT. Asaba) - Andila Rahma Putri; Dwi Arini; Fajrin Fajrin; Defwaldi Defwaldi (Jurnal Sains dan Ilmu Terapan, 2025)
Due to the rapid development of mapping technology using lasers, especially in the context of indoor mapping, such as Terrestrial Laser Scanners and Handheld SLAM LiDAR, it is necessary to understand the advantages and disadvantages of each technology. Therefore, it is necessary to validate both technologies to ensure their accuracy and reliability. The objective of this study is to identify the accuracy of the data produced by Terrestrial Laser Scanners and Handheld SLAM LiDAR by comparing the measurement results obtained using these methods with data obtained from an Electronic Total Station (ETS). The Total Station is used as a validation tool because of its higher accuracy compared to the LiDAR technology used in Terrestrial Laser Scanners and Handheld SLAM LiDAR.